Chapter The territorialisation of the 2030 Agenda: a multilevel approach - Attanasio, Raffaele (Proceedings e report, 2023)
The United Nations 2030 Agenda increasingly represents a reference point for political planning, as demonstrated by the centrality of the Sustainable Development Goals (SDGs) in the new cycle of EU policies. According to the European Committee of the Regions, 65% of the Agenda's objectives will not be achieved without the involvement and coordination of subnational governments. It is therefore necessary for the territories to adapt their programmatic tools in order to make them coherent with European and national programming, through the definition of a methodology capable of conforming the tools of local programming with those defined at the higher territorial levels. The aim of this paper is to present the methodological framework defined by the Italian Alliance for Sustainable Development (ASviS), based on the numerous experiences with local administrations, to support the implementation of multilevel sustainable local development strategies which make territorial planning consistent with the national and the European programming. The basis for correct multilevel programming provides for a mapping of the local context with respect to the 17 SDGs also through the calculation of composite indices, capable not only of summarizing the degree of sustainability of the individual territories for each Goal, but also of comparing the performance between the different realities belonging to higher or lower levels. Based on these results, the public and private stakeholders are involved in identifying quantitative "outcome" objectives, needed to define the commitments of the territories and to monitor the impact of policies with respect to the achievement of the SDGs.